Identification of sweet potato (Ipomoea batatas L.) viruses in Costa Rica. - Valverde, Rodrigo; Moreira, Marco A. (Agronomía Mesoamericana, 2004)
A survey for sweet potato (Ipomoea batatas L.) viruses was conducted in five commercial fields in Costa Rica from February to May 2002. High percentage of plants showing virus-like symptoms were observed in three of the five commercial fields. Graft-inoculations of fieldcollected samples to the virus indicator plant Ipomoea setosa were conducted. Foliar samples from inoculated plants were tested serologically for Sweet potato feathery mottle virus (SPFMV) and Cucumber mosaic virus (CMV), by reverse transcription polymerase chain reaction (RT-PCR) for Sweet potato chlorotic stunt virus (SPCSV), and by molecular hybridization for Sweet potato leaf curl virus (SPLCV). The aphid-transmitted SPFMV was the most common virus detected. Other viruses detected included SPCSV and SPLCV. CMV was not detected in any of the samples tested. Mixed infections of SPFMV and SPCSV were detected in the 3 commercial fields with a high percentage of plants showing virus-like symptoms. The identity of SPCSV was confirmed by whitefly (Bemisia tabaci) transmissions and RNA analysis of selected RT-PCR positive samples.